The association of adult vaccination with the risk of cerebrovascular ischemia: A systematic review and meta-analysis - Tsivgoulis, Georgios; Katsanos, Aristeidis H.; Zand, Ramin; Ishfaq, Muhammad Fawad; Malik, Muhammad Taimur; Karapanayiotides, Theodore; Voumvourakis, Konstantinos; Tsiodras, Sotirios; Parissis, John (Journal of the neurological sciences, 2018)
There is mounting evidence supporting infection as an independent risk factor for ischemic stroke (IS), while preliminary data indicate that vaccination may prevent IS. We performed a systematic review and meta-analysis of available randomized clinical trials (RCTs) or prospective observational cohorts reporting associations of influenza vaccination (IV) and/or pneumococcal vaccination (PV) with IS. We identified a total of 12 studies (543,311 patients; 47.4% vaccinated). Vaccination was not related to the risk of IS (RR=1.06, 95%CI: 0.74–1.51, p=0.77), with no significant differences (p=0.26) among RCTs (RR=0.66, 95%CI: 0.30–1.47) and observational studies (RR=1.11, 95%CI: 0.76–1.61). Evidence of considerable heterogeneity was identified within observational studies (I2=98%), but not within RCTs (I2=0%). In subgroup analyses according to vaccination type, IV was associated with a significantly lower risk of IS (RR=0.87, 95%CI: 0.79–0.96, p=0.004) with moderate evidence of heterogeneity (I2=53%). No association was seen for PV (RR=1.38, 95%CI: 0.60–3.16, p=0.45), where considerable heterogeneity was identified (I2=97%). In the additional adjusted analyses of observational studies, vaccination tended to be associated with lower risk of IS (HRadjusted=0.87; 95%CI: 0.75–1.01; p=0.07). The findings of this meta-analysis indicate that IV may be associated with a lower risk of IS. This association was not reproduced for PV or the combination of two vaccines. Substantial heterogeneity was detected across observational studies for all outcome events, while moderate to low heterogeneity was identified across included RCTs. These preliminary findings require independent validation in large RCTs. •Evidence support infection as an independent risk factor for ischemic stroke (IS).•Preliminary data also indicate that vaccination may prevent IS.•We investigated the aforementioned association in a systematic review/meta-analysis.•Influenza vaccination was found to be associated with a lower risk of IS.•Our finding requires independent validation in large RCTs.